Population impact of stricter adherence to recommendations for pharmacological and lifestyle interventions over one year in patients with coronary heart disease. Issue 12 (14th November 2005) - Gemmell, I; Heller, R F; McElduff, P; Payne, K; Butler, G; Edwards, R; Roland, M; Durrington, P
Abstract : Study objective: To assess the potential number of lives saved associated with the full implementation of aspects of the National Service Framework (NSF) for coronary heart disease (CHD) in England using recently developed population impact measures. Design: Modelling study. Setting: Primary care. Data sources: Published data on prevalence of acute myocardial infarction and heart failure, baseline risk of mortality, the relative risk reduction associated with different interventions and the proportion treated, eligible for treatment and adhering to each intervention. Main results: Adopting the NSF recommendations for pharmacological interventions would prevent an extra 1027 (95% CI 418 to 1994) deaths in post-acute myocardial infarction (AMI) patients and an extra 37 899 (95% CI 25 690 to 52 503) deaths in heart failure patients in the first year after diagnosis. Lifestyle based interventions would prevent an extra 848 (95% CI 71 to 1 614) deaths in post-AMI patients and an extra 7249 (95% CI 995 to 16 696) deaths in heart failure patients. Conclusions: Moving from current to "best" practice as recommended in the NSF will have a much greater impact on one year mortality rates among heart failure patients compared with post-AMI patients. Meeting pharmacological based recommendations for heart failure patients will prevent more deaths than meeting lifestyle based recommendations. Population impact numbers can help communicate the impact on a population of the implementation of guidelines and, when created using local data, could help policy makers assess the local impact of implementing a range of health care targets.